METODE PENGEMBANGAN INSTRUMEN PENGUKUR KECERDASAN SPIRITUAL MAHASISWA - Rijal Firdaos (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2017)
SPIRITUAL INTELLIGENCE MEASUREMENTS INSTRUMENT DEVELOPING METHODS. The main objective of this study is to provide information related how to develop an instrument spiritual to measure the intelligence of students. The specific objectives are: 1) understanding the instrumental development concept, 2) knowing the instrumental development procedure, 3) and determining the testing method. This study used library research by examining the literature as a supporting source. The results of study show that first, the instrument plays a very important role to determine the quality of a study, as well as become the tools used by researcher to collect the data by conducting measurements. Second, the instrumental development procedure passes several stages; those are developing the conceptual definition, giving scale, reviewing the justification points, preparing instrumental draft, collecting the trial data, and analyzing the trial data. Third, the testing method used to develop the instrument is factor analysis by using SPSS and Lisrel.